Calculation and Evaluation for the n+51V Reaction. (4th May 2017) - Guo, Hairui; Xu, Yongli; Han, Yinlu; Shen, Qingbiao; Ye, Tao; Sun, Weili
Abstract: A set of optical model potential parameters for the n+ 51 V reaction is obtained based on the experimental data of the total cross section, elastic scattering cross section, and elastic scattering angular distribution at incident energies up to 300 MeV. All cross sections, angular distributions, energy spectra, and double-differential cross sections for the n+ 51 V reaction are consistently calculated and analyzed at incident neutron energies below 250 MeV. The theoretical nuclear models including the optical model, distorted wave Born approximation theory, Hauser-Feshbach theory, evaporation model, exciton model, and intranuclear cascade model are used in the analysis. The calculated results are compared with the experimental data and the evaluated results in ENDF/B-VII.1 and JENDL-4.